2019
DOI: 10.12740/pp/90648
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Postoperative Cognitive Dysfunction (POCD) – Systematic Review

Abstract: WstępCelem tego systematycznego przeglądu było podsumowanie obecnej literatury na temat upośledzenia funkcji poznawczych u osób dorosłych po zabiegach operacyjnych.Materiał i metodyPrześledzono bazy MEDLINE: PubMed, OVID, Web of Science, EBSCO, używając odpowiednich słów kluczowych. Dokonano przeglądu literatury na temat zaburzeń poznawczych po zabiegach operacyjnych oraz analizy czynników ryzyka wystąpienia POCD.WynikiPrześledzono wyniki z siedmiu artykułów opisujących badania neuropsychologiczne 2796 pacjen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 37 publications
2
33
1
8
Order By: Relevance
“…POCD is a risk factor that results in a longer hospital stay, a lower likelihood of a return to independent living, and increased mortality [19]. An international trial of elderly patients (median age 68, range 60-81 years) demonstrated the incidence of POCD could be up to 26% within 7 days after non-cardiac surgery, and advanced age and length of anesthesia time were highly related with POCD [20].…”
Section: Discussionmentioning
confidence: 99%
“…POCD is a risk factor that results in a longer hospital stay, a lower likelihood of a return to independent living, and increased mortality [19]. An international trial of elderly patients (median age 68, range 60-81 years) demonstrated the incidence of POCD could be up to 26% within 7 days after non-cardiac surgery, and advanced age and length of anesthesia time were highly related with POCD [20].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical diagnosis of POCD involves a series of neuropsychological tests. However, there is no unified standard concerning the selection of tests, main reference points and follow-up duration, leading to different prevalent rates of POCD in different institutions [3]. Therefore, systemic, effective and simple diagnostic criteria should be developed for POCD.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative cognitive dysfunction (POCD) is a well-recognized phenomenon affecting patients of any age undergoing surgical procedures 1,2 . This cognitive decline can be observed among 5 to 40% of patients 3 , lasting few days to several months after surgery 4 . It impacts numerous cognitive abilities such as attention, speed of information processing, executive function, ability to combine tasks, psychomotor dexterity and memory 5,6 .…”
mentioning
confidence: 95%